Physicochemical and Organoleptic Characteristics of Taro (Colocasia esculenta) Flour Dried Noodles with the Addition of Kale Leaf Extract (Brassica oleracea var. sabellica): Karakteristik Fisikokimia dan Organoleptik Mie Kering Tepung Talas (Colocasia esculenta) dengan Penambahan Ekstrak Daun Kangkung (Brassica oleracea var. sabellica) - Ocviyanti Hendra Rezky -; Nanik Suhartatik; Vivi Nuraini (Agrobiotek, 2024)
Dried noodles made from egg and flour that have round and long shape. In this research, dried noodles were made differently in general because of using taro flour and kale leaves extract as a raw material. Taro flour is a gluten free flour that is rich in fiber. Kale (Brassica oleracea var. sabellica) is superfood which have high quantity of antioxidants like vitamin C and flavonoids. This research aimed to determine physicochemical and organoleptics characteristic of dried noodles of taro flour with addition of kale leaves extract. The observation used a two-factors factorial Completely Randomized Design (CRD) were the ratio of taro flour : wheat flour (85:15, 75:25, 65:35g) and the concentration of kale leaves extract (1:10, 2:10, 3:10 ml) with two-replication. The best results showed that the combination of 65:35 taro flour : wheat flour with addition of 3:10 kale leaves extract was based on high antioxidant activity. The results of this combination showed moisture content 5,42%, ash 2,74%, fiber 7,43%, protein 7,56%, antioxidant activity 13,71%, flavonoid total 1,36 mgQE/g, vitamin C 30,8%, color L* 78,72, color a* -1,78, color b* 18,11, hardness 13,84 N, chewiness 13,29 N, aroma 3,36 and kale taste 3,12. Based on the observation, dried noodles of taro flour with kale leaf extract influenced all physicochemical and organoleptic test results.